A systemic review of brucellosis in the Kakheti region of the country of Georgia: an evaluation of the disease ecology, risk factors and suggestions for disease control - Havas, Karyn Alicia, author; Salman, Mo D., advisor; Hill, Ashley E., committee member; Magennis, Ann L., committee member; Callan, Robert J., committee member; Gillette, Shana C., committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: agent based model; zoonotic; rapid assessment; Brucellosis